Aseptic Zero Discharge Fluid Dynamic Gauging for Measuring the Thickness of Soft Layers on Surfaces. Issue 10 (5th September 2016) - Wang, Shiyao; Schlüter, Florian; Gottschalk, Nathalie; Scholl, Stephan; Wilson, D. Ian; Augustin, Wolfgang
Abstract: A bench‐top device that can be used to perform fluid dynamic gauging measurements of soft solid layers with zero net liquid discharge and potentially under aseptic (closed system) conditions is demonstrated. Test results are presented for Newtonian liquids with a range of viscosities: deionized water, sucrose solutions, glycerol/water solutions and paraffin oil. The experimental data for discharge coefficient C d against clearance/nozzle throat diameter gave good agreement with CFD simulations and literature. The influence of surface roughness was studied by making measurements on a series of commercial sandpapers. The rough surfaces gave rise to systematic differences in C d from those obtained with smooth substrates. Careful calibration is required when gauging rough surfaces. Abstract : For performing fluid dynamic gauging measurements of soft solid layers with zero net liquid discharge and potentially under aseptic conditions a bench‐top device is presented. Newtonian liquids with a range of viscosities were used as test materials. By making measurements on a series of commercial sandpapers the influence of surface roughness was studied.